What factors are limiting financial inclusion and development in Peru? Empirical evidence - Sergio Luis Ná\~nez Alonso; Javier Jorge-Vazquez; Lieslie Gallegos Arias; Noelia Mu\~noz del Nogal (Economies, 2024)
Despite recent efforts in Peru to boost financial inclusion, significant issues of exclusion persist, especially among vulnerable groups. This article aims to identify and analyze areas at risk of financial exclusion using a multifaceted methodology: the Financial Access Survey (FAS) for comparative analysis (Peru versus other countries and regions), geographical-distribution analysis, and the Access to Cash Index (ACI) methodology. Findings reveal that remote rural areas of Peru, particularly those inland, as well as mountainous or jungle regions, face higher risks of financial exclusion due to low digital literacy, limited digital banking usage, sparse branch and ATM networks, and inadequate transportation infrastructure. These insights can inform targeted public policies to enhance financial inclusion in Peru, as well as the development.
Keywords: 330; access to credit; bankarization; economic development; financial exclusion; financial inclusion; inclusive development